Tinjauan Yuridis Terhadap Putusan Bebas (Vrijspraak) dalam Perkara Tindak Pidana Pembunuhan - Nurestu, Muthia Aulia Alyda; , Dr. Natangsa Surbakti, S.H., M.Hum (2017)
Judges play an important role in the trial due to the authority to examine, adjudicate and deciding a case that is required to seek the values of justice in the application of a progressive and responsive law judge in decisions must considering a wide range of considerations. At Article 183 Criminal Procedure Code contains several elements of consideration in deciding. In the case of acquittal, the judge requires foresight and rigor to considering a thing should really be convincing. This research is a doctrinal method that take expert opinion regarding the acquittal and through a legal product in the form of legislation and the decisions of the judges. The data used is secondary data. Secondary sources of data include primary, secondary, and tertiary legal materials. For primary legal materials, the data collection techniques used are literature, study of documents and interviews with the judge of the District Court of Surakarta. Furthermore, the data were analyzed using qualitative and inductive syllogism. Keyword: Consideration of the judge, Acquittal, Vrijspraak